The disagreement reasons about belief in predestination between Ahl Al-Sunnah Wa’l-Jama’ah and those who oppose them (review & study) - Al Ahmed, Saad Ibrahim Abdullah (Journal of Islamic Sciences, 2023)
The research aimed to explain the reasons for the disagreement in belief in predestination between the Sunnis and the community, and the offenders who oppose them. The research used the descriptive analytical approach, and the researcher used the descriptive analytical approach. And God’s exaltation of injustice, the ability and the unbearable assignment, and the actions of the servants, with a statement of the belief of the people of Sunnah and the community in every issue, and the sayings of those who oppose them in that issue. With absolute recognition of it, and their opponents confined themselves to some of the evidence that caused them to err by inferring those legal texts on these issues, and the teams differed in the matter of belief in predestination, so fatalism believes that the servants are forced to do their deeds, they have no power, will, or choice, and God alone is the Creator The actions of the servants, and the Mu'tazila believe that the actions of the servants are not created by God, but rather the servants are the creators of them, and the servant is independent of his work in will and power, and the Sunnis and the community agreed that the servants are commanded by what God commanded, and they forbid what God forbade, and they agree to believe in His promise and His threat that The Book and the Sunnah spoke of it, for people do not will except that God wills.
Keywords: belief; predestination; offenders; Sunnah